Adrenoleukodystrophy: Childhood and Adult Forms Compared - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Saturated, very long-chain fatty acids in erythrocyte membranes, blood plasma, and mononuclear cells were studied in 4 patients with childhood-adolescent adrenoleukodystrophy, 4 patients with adult adrenoleukodystrophy and 19 normal control subjects in the Department of Neurology, National Chikugo Hospital and the Neurological Institute, Kyusu University, Fukuoka, Japan.